Some mineralogical characteristics of a toposequence of soils from São Pedro region, São Paulo State - Demattê, J.L.I.; Holowaychuck, N. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
Eight pedons representing soils found on successively higher landscapes along a 25 km transect north of Piracicaba River were investigate as to their clay mincralogical properties. The clay fraction in most of the soils is composed predominantly of kaolinitc and gibbsite. Gibbsite is most prevalent in the soils exhibiting the most weathering. Pedons located on lower surface have a content of gibbsite of less trail 6% and pedons located on higher surfaces i, e. Pedons 6, 7 and 8, have a gibbsite content within the range of 12 - 54%. Pedons 3 has a different mincralogical coposition; the amount of 2:1 minerals represented by mica, vermic.ulite and montmorillonite is large, estimated values ranging from 30 to 70% of the clay. In the other soils the 2:1 mineral is represented mainly by vermieulitc in low amounts (less than 8%) and it is lower in soils on the higher surfaces. For the lower surfaces there is a correlation between clay mineralogy and the pustulated relative ages of surface. This relationship is not apparent in soils located on the higher surfaces. Transformation of kaolinite to gibbsite is suggested by the results obtained on relative quantities of these mineral species found in the soils investigated.